Perceptions of teachers and students about the new social studies in two selected schools - Romero, Frisca Arceo
This study determined the perceptions of teachers and students of social studies in two selected schools, Ramon Magsaysay (Cubao) High School and UP High Preparatory School in relation with the other academic subjects taken by the seniors. It surveyed the perceptions of the eight teachers of social studies handling the seniors.